Diagnosis of Herpes Zoster Using Bayes Theorem Method - Frisca Prastiwi, Kellyn; Novriyenni; Khair, Husnul (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Expert Systems is one branch of Artificial Intelligence (AI) that makes widespread use of knowledge or knowledge specifically for solving expert human-level problems. Kartini Clinic has several health workers such as nurses, midwives to doctors who are ready to serve people who suffer from various diseases, one of which is Herpers Zoster disease. Shingles is an acute inflammation of the skin usually characterized by the appearance of red bubbles like small blisters that cluster on the surface of the skin and watery and accompanied by itching and heat. This disease will appear more if there is irritation, wounds or abrasions and a long healing process. Bayes' theorem is a mathematical equation used in probability and statistics to calculate conditional probabilities.